Eduardo Neira Alva and Brazil: approximations, reflections and proposals for social housing and urban planning in times of hope, 1965-1974 - Espinoza José Carlos Huapaya (Risco - Journal of Architecture and Urbanism, 2016)
The performance of Latin American professionals held in own Latin American countries is still a subject little explored by the specialized historiography. From this background, we can raise the following questions: what is the role of Latin American professionals in the construction of Latin American cities? Which the local contribution and resonance of Latin American professionals who have worked and circulated by several countries of the continent? This article aims to understand the professional contribution of Eduardo Neira Alva in Brazil between 1965 and 1974, a period which was linked to the IDB and the Government of the State of Bahia, a fact that enabled him to produce a series of studies and projects in the metropolitan area from Salvador.